Measuring the impact of marketing capability and market control beliefs on marketing strategy intention: a study on travel and tour agents in Malaysia - Haque, A. K. M. Ahasanul; Ahmed, Faruk; Al-Sarwar, Abdullah Mamun; Shafiq, Ali (Inderscience Publishers, 2017)
The aim of this paper is to measure the effect of marketing capability and market control beliefs on marketing strategy intention in strategising Islamic travel and tour packages of travel and tour agents from the perspective of Malaysia. The research revealed that innovativeness, communication, collaboration and cooperation, and control beliefs significantly affect marketing strategy intention through the mediators of marketing capability attitude and market control capability. As a quantitative research approach, from a sampling frame of 420 travel and tour enterprises around Malaysia, 107 respondents were successfully surveyed through a self-administered questionnaire. The result would be useful for practitioners in terms of understanding the effects and magnitude of those variables in developing Islamic travel and tour package in the Islamic tourism industry of the Islamic countries. The effort was employed, for the first time, in this type of perspective. So perhaps, this would have a new horizon of theoretical understanding of the strategic Islamic tourism conceptualisation under the theory of planned behaviour. Keywords: Islamic tourism; Islamic travel and tour package; travel and tour agents; marketing strategy intention; partial least square; PLS; Malaysia.